STRATEGI PENULISAN ARTIKEL ILMIAH UNTUK LOLOS PUBLIKASI JURNAL TERAKREDITASI SINTA BAGI MAHASISWA BIDANG TEKNIK - Ariyanto, Sudirman; Cahyadi, Wahyu; Nugraha, Ata (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2023)
The publication of scientific articles in accredited journals plays a central role in the academic world, especially for engineering students. While previous Community Service (Pengabdian Kepada Masyarakat or PKM) activities focused on enhancing students' understanding and skills related to scientific article writing, this PKM identifies specific needs of engineering students for more comprehensive training and mentoring. In order to meet these needs, the PKM organizes specialized training and mentoring for engineering students. Evaluation is conducted by measuring the quality of article writing, language clarity, scientific contribution, and adherence to the guidelines of the SINTA indexed journals. The PKM stages involve the collection of initial data, training implementation, assignment of article writing tasks, technical mentoring, and evaluation using assessment instruments. The results of the PKM activities have significantly improved the quality of student writing. Scores for article quality, language clarity, scientific contribution, and adherence to the guidelines of SINTA indexed journals have increased, reflecting the students' ability to produce better articles. Overall, this PKM activity makes a significant contribution to enhancing the abilities of engineering students in writing scientific articles that meet the standards of accredited SINTA journals. The relevance of this improvement is not only limited to meeting graduation requirements but also extends to the students' contribution to the development of knowledge in the field of engineering.